Bifurcation of Corporate Management: Traditional and Innovation Logics - X. V. Sadykova (Вестник Российского экономического университета имени Г. В. Плеханова)
In conditions of the global management crisis caused by COVID-19 the issues dealing with management efficiency become especially topical. Integrated corporate structures embracing big banks and corporations make the basis both for economic and political force. Though the disintegration strategy is becoming more and more popular, multinational companies are not weakened and continue influencing governments of many countries of the world. Decisions made in these organizations can impact not only economy of a certain country, its ecology, social policy but often the future of states and regions. That is why corporate strategies, which should be relevant to present day realities, become so important. Today the majority of integrated corporate structures stick to traditional logics in corporate management realizing it within the frames of Freedman theory. The article compares and summarizes traditional and innovation theories of corporate management, shows their advantages and drawbacks, analyzes the experience of big global companies and provides legal substantiation of splitting responsibility inside corporations. An attempt was made to prove groundlessness of traditional logics of profit maximization in today’s world and to identify ways to shifting focus to the company development.